PROGNOSTIC VALUE OF HYPERREFLECTIVE FOCI IN NEOVASCULAR AGE-RELATED MACULAR DEGENERATION TREATED WITH BEVACIZUMAB. Issue 11 (November 2016) - Segal, Ori; Barayev, Edward; Nemet, Arie Y.; Geffen, Noa; Vainer, Igor; Mimouni, Michael
Abstract : Purpose: To study the prognostic value of optical coherence tomography hyperreflective foci (HF) in neovascular age-related macular degeneration. Methods: Charts of naive neovascular age-related macular degeneration eyes treated with intravitreal bevacizumab between January 2011 and January 2014 were reviewed, and optical coherence tomography was collected at baseline, 3 months, and 12 months. The presence, location (inner vs. outer retinal layers), and number (few = [0–10], moderate [11–20], many [>20]) of HF were graded. Results: Overall, charts of 111 eyes were reviewed and 76 eyes of 73 patients fulfilled inclusion criteria. Baseline best-corrected visual acuity was lower in eyes with HF > 20 ( P = 0.001), inner layer HF ( P = 0.009), increased central retinal thickness ( P < 0.001), and intraretinal fluid ( P < 0.001). Baseline HF > 20 ( P = 0.002), inner layer HF ( P = 0.01), increased central retinal thickness ( P < 0.001), and intraretinal fluid ( P = 0.001) had worst best-corrected visual acuity at 12 months. Eyes with intraretinal fluid, HF > 20, and HF adjacent to intraretinal fluid demonstrated a greater reduction in central retinal thickness; only baseline HF > 20 remained significant in multivariate analysis ( P < 0.001). Eyes with a reduction in HF ( P = 0.02) and resolution of inner layer HF ( P = 0.01) had a greater central retinal thickness reduction. Conclusion: Quantity and location of HF are of prognostic value in intravitreal bevacizumab–treated naive neovascular age-related macular degeneration. Increased awareness of specialists interpreting optical coherence tomography scans toward the number and location of HF is prudent. Abstract : Naive neovascular age-related macular degeneration eyes treated with bevacizumab who had >20 hyperreflective foci and involvement of the inner retinal layers on optical coherence tomography had a worst best-corrected visual acuity after 12 months. Increased awareness of specialists interpreting optical coherence tomography scans toward the number and location of hyperreflective foci is recommended.